2019
DOI: 10.1177/1740774519829709
|View full text |Cite
|
Sign up to set email alerts
|

A review of the impact of utilising electronic medical records for clinical research recruitment

Abstract: Introduction: Recruitment is an important aspect of clinical research, as poor recruitment could undermine the scientific value of a trial or delay the development process of new treatments. The development of electronic medical records provides a new way to identify potential participants for trials by matching the eligibility criteria with patients’ data within electronic medical records. Methods: A literature search was performed to examine the effectiveness and efficiency of the electronic medical record r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 72 publications
(100 reference statements)
1
24
0
1
Order By: Relevance
“…Though limited, evidence suggests that RWD-supported recruitment strategies-such as direct email campaigns to patients identified through claims data and EHR-supported discussions at the point of care-have the potential to increase recruitment effectiveness and efficiency for many trials [15,16]. CTTI recommends incorporating RWD-supported recruitment, alongside traditional modes of recruitment, whenever available data are fit for purpose.…”
Section: Using Rwd To Support Recruitmentmentioning
confidence: 99%
“…Though limited, evidence suggests that RWD-supported recruitment strategies-such as direct email campaigns to patients identified through claims data and EHR-supported discussions at the point of care-have the potential to increase recruitment effectiveness and efficiency for many trials [15,16]. CTTI recommends incorporating RWD-supported recruitment, alongside traditional modes of recruitment, whenever available data are fit for purpose.…”
Section: Using Rwd To Support Recruitmentmentioning
confidence: 99%
“…To enhance the identification and recruitment of participants into clinical trials, new tools have been created for convenient, data-driven insights in the available patient population. Due to recent advances in Electronic Health Record (EHR) query technology, the use of EHR data for patient recruitment is currently seen as a promising tool to improve identification and recruitment of trial participants [ 6 , 7 ]. An EHR is an individual patient record contained within a hospital's electronic patient record system.…”
Section: Introductionmentioning
confidence: 99%
“…Pragmatic randomized trials enriched with routinely collected EHR data are considered to have the potential to be less costly and produce more generalizable results (e.g., a large sample size, efficient recruitment from the patient populations, and longer follow-up time) than traditional randomized trials [2932]. A recent review found that the use of the EHR data for clinical trial recruitment was an effective method due to its capability for patient identification outside working hours and fast processing time [33]. However, the completeness and accuracy of the EHR data must be evaluated and addressed in order to fully realize the potential of leveraging the EHR data for health care quality improvement and research efforts [293233].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review found that the use of the EHR data for clinical trial recruitment was an effective method due to its capability for patient identification outside working hours and fast processing time [33]. However, the completeness and accuracy of the EHR data must be evaluated and addressed in order to fully realize the potential of leveraging the EHR data for health care quality improvement and research efforts [293233]. For example, a study analyzing 351 eligibility criteria from 15 clinical trials found that clinical data was available for 64 percent of all patients and that the total completeness of EHR data for recruitment purposes was just 35 percent [34].…”
Section: Introductionmentioning
confidence: 99%